Very high PD‐L1 expression as a prognostic indicator of overall survival among patients with advanced non‐small cell lung cancer receiving anti‐PD‐(L)1 monotherapies in routine practice. Issue 10 (22nd June 2022) - Shah, Mohsin; Hubbard, Rebecca A.; Mamtani, Ronac; Marmarelis, Melina E.; Hennessy, Sean
Abstract: Purpose: Programmed death or ligand‐1 (PD‐(L)1) pathway inhibitors confer improved survival as the first‐line treatment for advanced non‐small cell lung cancer (aNSCLC) in patients with PD‐L1 expression (PD‐L1 + e ≥ 50%) compared to platinum‐doublet chemotherapy and have become a standard therapy. Some recent evidence suggests that among aNSCLC patients with PD‐L1 + e of ≥50% receiving pembrolizumab monotherapy, very high levels of PD‐L1 + e (≥90%) may be associated with better outcomes. We sought to assess whether very high PD‐L1 + e (≥90%) compared to high PD‐L1 + e (50%–89%) is associated with an overall survival benefit in aNSCLC patients receiving anti‐PD‐(L)1 monotherapies. Methods: We conducted a single‐site retrospective cohort study of aNSCLC patients who initiated PD‐(L)1 inhibitor monotherapy as the first‐line treatment from October 24, 2016, to August 25, 2021, and had a PD‐L1 + e ≥ 50%. The primary outcome was overall survival, measured from the start of the first‐line PD‐(L)1 inhibitor monotherapy (index date) to date of death or last confirmed activity prior to the cohort exit date. Propensity score‐based inverse probability weighting (IPW) was used to control for confounding in Kaplan–Meier curves and Cox proportional hazard regression analysis. Results: One hundred sixty‐six patients with aNSCLC receiving PD‐(L)1 inhibitor monotherapy met inclusion criteria. 54% were female, 90% received pembrolizumab, median age was 68 years, 70% had non‐squamous cell carcinoma, 94% had a history of smoking, 29% had a KRAS mutation, and 37% had very high PD‐L1 + e. Unweighted covariates at cohort entry were similar between groups (absolute standardized mean differences [SMDs] <0.1) except for race (SMD = 0.2); age at therapy initiation (SMD = 0.13); smoking status (SMD = 0.13), and BRAF mutation status (SMD = 0.11). After weighting, baseline covariates were well balanced (all absolute SMDs <0.1). In the weighted analysis, having a very high PD‐L1 + e was associated with lower mortality (weighted hazard ratio 0.57, 95% CI 0.36–0.90) and longer median survival: 3.85 versus 1.49 years. Conclusions: Very high PD‐L1 + e (≥90%) was associated with an overall survival benefit over high PD‐L1 + e (50%–89%) in patients receiving the first‐line PD‐(L)1 inhibitor monotherapy in a model controlling for potential confounders. These findings should be confirmed in a larger real‐world data set.